Integrasi Matematika dan Filsafat Pendidikan Islam - Basori Basori; Dearezha Priska; Reza Alinata; Yuli Kartika Putri (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
This article explores the nature of the philosophy of Islamic education and its integration with the philosophy of mathematics in the learning process. The philosophy of Islamic education is rooted in the Qur’an and As-Sunnah and is further reinforced by the thoughts of Muslim philosophers. It encompasses three main aspects: ontology (the nature of existence), epistemology (the sources and methods of acquiring knowledge), and axiology (values and purposes). Islamic education aims not only to shape individual character but also to build a holistic educational system based on Islamic values. In this context, education is not merely a process of knowledge transfer but a means of fostering moral and spiritual development in learners. On the other hand, the philosophy of mathematics from the perspective of Islamic education emphasizes that mathematics is not solely an exact science of arithmetic, but also a discipline closely related to ethical and moral values in Islam. Mathematics is viewed as part of the divine order of Allah’s creation, reflecting His greatness. Therefore, the integration of Islamic educational philosophy and mathematical philosophy in learning offers a deeper approach to mathematical concepts. This approach not only enhances students’ cognitive understanding of the material but also instills spiritual awareness and values of faith and piety. By combining scientific and religious aspects, the learning process becomes more systematic, meaningful, and aligned with the comprehensive goals of Islamic education.